Transformasi Pendidikan Islam dalam Mengantisipasi Dampak Negatif Budaya Instan dan Hipokrisi Digital: Telaah Al-Qur’an, Hadis dan Perpektif Keilmuan - Mushofa, Mushofa; Fidzi, Ridhani; Hamdan, Hamdan; Ma’ruf, Hidayat (Green Publisher Indonesia, 2025)
The development of instant culture and digital hypocrisy has affected the mindset and character of individuals, especially in the world of education. This phenomenon poses a challenge for Islamic education in forming an authentic personality, integrity, and moral resilience. This study aims to analyze the transformation of Islamic education in facing the negative impact of instant culture and digital hypocrisy by studying the Qur'an, hadith, as well as psychological, sociology, and anthropological approaches. Using a qualitative method based on literature studies, this study examines relevant primary and secondary sources. The results of the study show that Islamic education needs to instill the values of patience, honesty, and exemplary as an antidote to instant culture and digital hypocrisy. In addition, a learning strategy based on character education, critical digital literacy, and strengthening the educational environment that supports self-awareness and moral responsibility is needed. With this approach, Islamic education can play a role in shaping an adaptive, critical, and noble generation in the digital era.